1998
DOI: 10.1212/wnl.50.6.1715
|View full text |Cite
|
Sign up to set email alerts
|

SPECT study of a German CADASIL family

Abstract: We describe a CADASIL phenotype that is characterized by the absence of focal neurologic symptoms and present the first SPECT study of this disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
1
4

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 0 publications
4
34
1
4
Order By: Relevance
“…36 Assuming a constant diameter of the MCA, the MFV reduction in our CADASIL cases may essentially reflect reduced CBF. In fact, a reduction of CBF has been suggested recently by SPECT, 12 PET, 13 and MRI studies 20 in CADA-SIL. It seems reasonable to assume that the changes in MFV and CBF are related to the morphological alterations within small blood vessels, in particular small arteries and capillaries.…”
Section: Discussionmentioning
confidence: 96%
“…36 Assuming a constant diameter of the MCA, the MFV reduction in our CADASIL cases may essentially reflect reduced CBF. In fact, a reduction of CBF has been suggested recently by SPECT, 12 PET, 13 and MRI studies 20 in CADA-SIL. It seems reasonable to assume that the changes in MFV and CBF are related to the morphological alterations within small blood vessels, in particular small arteries and capillaries.…”
Section: Discussionmentioning
confidence: 96%
“…This suggests that the severity and extent of SMC loss in the cerebral arteries progress at the shift from the nonsymptomatic to the symptomatic state. In addition, it has been reported that there is a reduction in blood flow to the cerebrum 4 and in the middle cerebral artery 11 in CADASIL, but these findings may merely reflect the final devastated state of the brain. Cerebrovascular reactivity to fluctuations not only in CO 2 but also in systemic blood pressure during the clinical course of CADASIL should be examined further.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 However, there are some phenocopies in which such a mutation is not recognized but in which deposition of GOM has been noted pathologically. 4 Therefore, the origin of CADASIL seems to be genetically heterogeneous. Neuropathologically, diffuse myelin loss, atrophy of the cerebral white matter with sparing of the subcortical U fibers, and small infarcts in the subcortical gray matter are all characteristic of CADASIL but not specific to it; these pathological signs are also seen in association with acute carbon monoxide poisoning, a potential hazard of general anesthesia such as in accidents of artificial ventilation, amyloid angiopathy, and Binswanger's disease.…”
mentioning
confidence: 99%
“…A reduction of cerebral blood flow (CBF) has been documented in the cortex and white matter in CADASIL patients using PET (31), SPECT (32), and MRI bolus tracking (33). We measured resting CBF in awake TgNotch3 R169C mice and control TgNotch3 WT and nontransgenic littermate mice by quantitative autoradiography using a diffusible radiolabeled tracer, which provides a measure of local tissue perfusion through brain microvascularization (Supplemental Figure 6 and Supplemental Table 1).…”
Section: Figurementioning
confidence: 99%